Windows security monitoring : scenarios and patterns - Miroshnikov, Andrei (Indianapolis, IN : John Wiley & Sons, Inc., 2018)
With expert guidance to bring you up to speed on Windows auditing, logging, and event systems to help you exploit the full capabilities of these powerful components, this book offers scenariobased instruction providing clear illustration of how these events unfold in the real world. --
Includes index.
Online resource; title from PDF title page (EBSCO, viewed March 21, 2018).
Includes bibliographical references and index.
Keywords: Microsoft Windows (Computer file); Microsoft Windows (Computer file); Computer security; COMPUTERS -- Security -- General; Computer security; Electronic books